METHODICAL ASPECTS OF EVALUATING THE COST OF CROWDFUNDING CAPITAL (INNOVATIVE ECONOMY, 2019)
Kuts L.L. METHODICAL ASPECTS OF EVALUATING THE COST OF CROWDFUNDING CAPITALPurpose. The purpose of the article is to explore the possibilities of different models of crowdfunding in the formation of equity or loan capital to finance the projects of companies, to develop methodological aspects of the evaluation of the benefits of crowdfunding in comparison with alternative sources of financing.Methodology of research. General scientific and special methods are used in the research, in particular: analysis and synthesis, theoretical generalization, abstract and logical - in the study of the spectrum of modern sources of capital and their value in financing projects with the implementation of innovative - crowdfunding; the contribution of various crowdfunding models to the formation of equity or debt capital to finance company projects; systematizing the types of costs associated with crowdfunding; economics and mathematics - when developing methods of estimating the cost of crowdfunding capital for different models of crowdfunding.Findings. Possibilities of different models of crowdfunding in formation of equity or loan capital of companies along with traditional sources of capital are investigated. Methods for estimating the cost of attracting different types of crowdfunding capital are proposed based on a modification of the methods of calculating the cost of relevant traditional sources of capital, which will help more rational use of crowdfunding when financing companies' projects.Originality. The possibilities of different models of crowdfunding in formation of equity or loan capital for financing of projects of companies are substantiated. The spectrum of costs of companies for crowdfunding is systematized, which serves as a basis for methods of calculating its value as a source of capital. Methods for calculating the cost of crowdfunding capital in terms of its various models are proposed.Practical value. The findings of the study are aimed at solving the problem of managing the crowdfunding capital of project developers and will facilitate informed making decision in this area. They can be used to manage project funding at different levels.Key words: crowdfunding; crowdfunding capital; cost of crowdfunding capital; innovation; financing.
Keywords: Key words; crowdfunding; crowdfunding capital; cost of crowdfunding capital; innovation; financing.